Impact of lead on Catalpa bignonioides and Paulownia tomentosa and its phytoremediation ability - N. V. Nuzhyna; N. V. Henzerska; H. O. Rudic; S. P. Kovalova; O. V. Dmytrenko (Regulatory Mechanisms in Biosystems, 2025)
Environmental pollution by heavy metals resulting from anthropogenic activities is an extremely important issue in the world. This problem is especially exacerbated d uring wars, which generate long-term ecological consequences that can affect human health and the environment for decades. Combat operations, destruction of industrial facilities, use of explosives and ammunition – all this leads to the release of significant amounts of toxic elements into the environment. One of the most dangerous of these is lead. Developing effective strategies to remediate soils from heavy metal cont a mination is critical to protecting public health and ensuring a sustainable future. The aim of our research was to analyse paulownia and catalpa for their resistance to lead and their phytoremediation ability. The p lants Catalpa bignonioides and Paulownia tomentosa were watered with a solution of lead acetate at the rate of 100 or 300 mg/kg soil. The state of the photosynthetic system (chlorophyll fluorescence measured using a fluorometer and the content of chlorophylls and carotenoids); and malondialdehyde as a stress index and peroxidase activity as an antioxidant enzyme were determined by spectrophotometric method; growth and lead content in plants were also measured. The photosynthetic system of paulownia was resistant to the action of lead: the activity of peroxidase, the efficiency of the dark phase of photosynth e sis and the content of chlorophyll b increase d , and the stimulation of plant growth wa s observed. L lead had a negative effect on catalpa: a decrease in the content of chlorophyll a and carotenoids, and in the efficiency of the light phase of photosynthesis and plant growth. Paulownia has shown the ability to phytoremediation, accumulating lead in the stem and root. Catalpa did not show any resistance to lead and phytoremediation capabilities.